‘See How the Blood is Settled in his Face’: Shakespeare’s Warwick – Fiction’s First Pathologist - Andrea Smith (Janeway JS, 2020)
The twenty-first century television detective drama often relies heavily on the forensic pathologist; analysing what they see and reaching a conclusion about the manner of death, not just the cause. This might include determining that a case that initially looks like natural causes is in fact murder. While this may involve toxicology reports and other modern methods of investigation, it might also include the state of the body; things like post-mortem lividity or marks such as scratches, or a lack of them. Using these sorts of indicators is not new; in fact Shakespeare was writing about them in the late sixteenth century in 2 Henry VI. In it, the Earl of Warwick describes the state of the body of the Duke of Gloucester who has reportedly died in his bed. Over the course of around twenty lines Warwick gives a detailed catalogue of the state of the body and why each sign indicates a violent, rather than peaceful, death. This paper looks at that description and relates it to other descriptions of murder victims in drama at the time, as well as to those investigated by twenty-first century television pathologists.